Türk borçlar hukuku ve idare hukuku açısından ölüm halinde manevi tazminat - Cabıoğlu, Saniye Sena (My University, 2012)
Çalışma konumuzu, Türk Borçlar Hukuku ve İdare Hukuku açısından ölüm halinde manevi tazminat oluşturmaktadır. Bu konuyu seçmekteki amacımız, özellikle ülkemizde kişilerin ölüm halinde oluşan acı, üzüntü ve ruhsal sarsıntılarını gidermede yetersiz kalan manevi tazminatı, Türk Borçlar Hukuku ve İdare Hukuku boyutuyla ele alarak konunun önemini vurgulamaktır. Bu kapsamda birinci bölümde, manevi tazminat kavramı açıklandıktan sonra manevi tazminatın amacı, hukuki niteliği ve Türk Borçlar Kanunu’ndaki yasal dayanakları ele alınacaktır. İkinci bölümde, 6098 sayılı Türk Borçlar Kanunu’na göre ölüm halinde manevi tazminat başlığı altında manevi tazminatın şartları ayrıntılı olarak açıklanacaktır. Üçüncü bölümde, manevi tazminat davasının tarafları incelenerek bu kapsamda kimlerin davacı ve davalı olabileceği irdelenecektir. Ayrıca Türk Borçlar Hukukuna göre manevi tazminatın belirlenmesi, manevi tazminat davasının tabi olduğu zamanaşımı süresi, manevi tazminat talebinin üçüncü kişilere devri ve mirasçılara geçmesi ile manevi tazminat davasında görevli ve yetkili mahkemeye ilişkin açıklamalar da bu bölümde yer alacaktır. Dördüncü bölümde ise ölüm halinde manevi tazminat idare hukuku boyutuyla ele alınacak, bu kapsamda idari yargı uygulamaları ve yapılan değişiklik incelenecektir. Ayrıca idarenin sorumluluk esasları açıklanarak yapılan değişiklik tartışılacak, ortaya çıkabilecek olan sorunlara çözüm getirilmeye çalışılacaktır.

This study focuses on non-monetary compensation (non-pecuniary damages) upon death in terms of Turkish Law of Obligations and Administrative Law. The purpose in picking up this topic is to discuss the matter of non-monetary compensation which remains insufficient to cure and remedy pains, sorrows and psychologica! disturbances suffered upon death of a person in our country, in particular, as well as to give bigger emphasis upon this matter. In this context, chapter one first clarifies the concept of non-monetary compensation and then deais with its purpose and legal nature, as well as with legal grounds as laid down in Turkish Law of Obligations. Chapter two details conditions for non-monetary compensation laid down in Turkish Law of Obligations 6098 under title of 'non-monetary compensation upon death', Chapter three deals with parties to a non-monetary compensation lawsuit, discussing who might be plaintiff and defendant to such a lawsuit. This chapter also gives explanations as to determination of non-monetary compensation according to Turkish Law of Obligations, statute of limitations imposed on non-monetary compensation lawsuit, and transfer of claims for non-monetary compensation to third parties, or conveyance thereof to heirs, as well as to courts having jurisdiction over non-monetary compensation lawsuits. And, finally, chapter four discusses non-monetary compensation upon death in terms of administrative law, dealing with administrative court practices and amendment made in that regard. It also clarifies principles of liability on the part of the Administration, discussing about the amendment made and proposing some solutions for problems likely to arise.
Keywords: Borçlar Hukuku; Hukuk; İdare Hukuku; Özel Hukuk